Students' influential factors in selecting private university for higher education in Bangladesh - Rahman, Mohammad Mizanur; Abdul, Mohani; Rahaman, Mohammad Saidur (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The main drive of this study is to identify the factors considered by the students while choosing a private university to get admission. In addition, it is the intention of the research to provide some directions and guidelines to the university authorities on what areas need to focus. This study is carried out by using a structured questionnaire taking a sample size of 200 collecting primary data from first year undergraduate students of different private universities located in Sylhet Division, Bangladesh. A number of statistical measures such as descriptive analysis, ANOVA test have been used to analyse the data to draw conclusions and offer recommendations. The results show that the influence of parents or guardians, friends in college or existing university, university educated relatives, university admissions representative, academic and university reputation, campus safety, and qualified faculties are the major influencing factors on the admission decision of a student to a specific university.